The Prevalence of Insufficient Sleep and Bedtime Delay Among Kindergarten Children Aged 3 to 6 Years in a Rural Area of Shanghai: A Cross-Sectional Study - Chen, Xi; Qiang, Yan; Liu, Xia; Yang, Qing; Zhu, Qingqing; Li, Bin; Wang, Ruiping (Frontiers in Pediatrics, 2021)
Introduction: Sleep deprivation in children is a global public health problem that affects children's physical and mental development. Bedtime delay induced by longer screen time and heavy study load is a common cause of sleep deprivation in children. However, the prevalence of insufficient sleep and bedtime delay and related influencing factors among kindergarten children is limited in Shanghai, China. Methods: We selected 8, 586 children aged 3 to 6 years and their parents in 2018 in Songjiang district, Shanghai. Data was collected by face to face questionnaire interview with signed informed consent. We defined insufficient sleep as those who slept less than 10 hours for children aged 3-5 years, or 9 hours for children aged 6 years within 24 hours, and children with bedtime after 21:00 was defined as bedtime delay. SAS 9.1.3 software was used to calculate the prevalence of bedtime delay and insufficient sleep, and logistic regression were used to explore potential influencing factors. Results: The prevalence of insufficient sleep and bedtime delay among children aged 3 to 6 years was 11.67% and 56.85%, respectively. The prevalence of insufficient sleep among boys was slightly higher than girls [OR =1.18, 95% CI (Confidence Interval) (1.04, 1.35)]. With the increase of children’ s age, the prevalence of insufficient sleep elevated gradually (P<0.05). The prevalence of insufficient sleep was higher among singleton children [OR=1.18, 95% CI (1.02-1.36)], and those with longer hours of TV watching [OR=109, 95% CI (1.02-1.16)]. Meanwhile, the prevalence of bedtime delay was higher among singleton children [OR=1.17, 95% CI (1.06-1.79)], among those with parents’ accompanying for sleep [OR=1.21, 95% CI (1.10-1.34)], and those with longer TV watching time [OR=1.13, 95% CI (1.07-1.18)]. Conclusions: Insufficient sleep and bedtime delay were prevalent in Chinese children aged 3 to 6 years, especially in boys and elder children. TV watching as well as parents’ accompanying for sleep were associated with insufficient sleep and bedtime delay. We recommend that parents should limit children’ screen time, advocate earlier bedtime and later morning wake up among children, as well as make their children sleep in separate beds or rooms in younger age.